Análisis del sistema de gestión ambiental basado en la norma técnica colombiana ISO 14001: 2015 para las empresas que realicen la fracturación hidráulica para la explotación de gas de lutitas (2017)
This paper aims to analyze the NTC ISO 14001: 2015 for companies engaged in hydraulic fracturing in shale deposits in Colombia. As a methodology, the requirements of the ISO 14001: 2015 standard applied to this type of company were used. The hydraulic fracturing technique benefits within the petroleum sector were found. However, the implementation of an environmental management system is not enough to control the environmental impacts generated by the practice, questioning the role of organizations in the management of their activities.